Bank presence, agricultural production, and climate resilience: Evidence from India - Bai, Liang; Boudot-Reddy, Camille; Butler, André; Eigner, Johannes (Journal of Banking & Finance, 2026)
We study the production effects of one of the largest bank branch expansion programs in history, implemented by the government of India during the 1980s. Combining policy-driven variation with newly-digitized data on bank lending and crop prices at the district-year level, we do not find evidence for a significant shift in agricultural output and inputs on average. Greater bank presence does promote resilience to climate risk, however, by attenuating the effect of lagged rainfall shocks on output. This effect operates via changes in the incidence of cropping during the dry winter season, which makes use of costly irrigation resources.